2017
DOI: 10.1111/ejn.13786
|View full text |Cite
|
Sign up to set email alerts
|

Motion contrast in primary visual cortex: a direct comparison of single neuron and population encoding

Abstract: Features from outside the classical receptive field (CRF) can modulate the stimulus-driven activity of single cells in the primary visual cortex. This modulation, mediated by horizontal and feedback networks, has been extensively described as a variation of firing rate and is considered the basis of processing features as, for example, motion contrast. However, surround influences have also been identified in pairwise spiking or local field coherence. Yet, evidence about co-existence and integration of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Whereas binocularity in lateral-eyed mammals, such as rodents, clearly depends on the integrity of the CC ( Pietrasanta et al, 2012 ; Andelin et al, 2020 ; Laing et al, 2015 ), there is evidence that global binocularity in the cat does not (e.g. Minciacchi and Antonini, 1984 ; Gardner and Cynader, 1987 ; Conde-Ocazionez et al, 2018a , b ). However, other studies showed the contrary (e.g.…”
Section: Lesions and Inactivationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Whereas binocularity in lateral-eyed mammals, such as rodents, clearly depends on the integrity of the CC ( Pietrasanta et al, 2012 ; Andelin et al, 2020 ; Laing et al, 2015 ), there is evidence that global binocularity in the cat does not (e.g. Minciacchi and Antonini, 1984 ; Gardner and Cynader, 1987 ; Conde-Ocazionez et al, 2018a , b ). However, other studies showed the contrary (e.g.…”
Section: Lesions and Inactivationsmentioning
confidence: 99%
“…This mechanism complements the interactions between crossed and uncrossed retino-geniculo-cortical pathways that subtend binocular and stereovision along but also beyond the visual midline, in the whole binocular visual field ( Hubel and Wiesel, 1967 ; Poggio and Poggio, 1984 ). This reasoning also applies when considering other attributes of the visual scene such as orientation, direction or spatial frequency encoded by the interconnected neurons ( Berardi et al, 1987 ; Rochefort et al, 2007 ; Ribot et al, 2013 ; Conde-Ocazionez et al, 2018a , b ).…”
Section: Lesions and Inactivationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We are proud to feature Kerstin and her superb work here in the European Journal of Neuroscience's ‘Profiles of Women in Science’ as we seek to increase the visibility and recognition of women neuroscientists across the globe (Helmreich et al ., ). Her latest work published in EJN (Conde‐Ocazionez et al ., ), ‘Motion contrast in primary visual cortex: A direct comparison of single neuron and population encoding’ can be found here: http://onlinelibrary.wiley.com/wol1/doi/10.1111/ejn.13786/full…”
mentioning
confidence: 99%